Studies on Colour Removal from Dye Aqueous Solution Using Modified Forms of Adsorbent Materials - A. Geetha (New Innovations in Chemistry and Biochemistry Vol. 4, 2021)
The potentiality of activated carbon (CSAC) and polypyrrole coated sawdust (PPy/SD) derived from the fruit of the gardening plant material of cordia sebestena to remove acid orange -7 from aqucous solutions via adsorption was investigated. The adsorption process provides an attractive alternative treatment, especially if the adsorbent is inexpensive and readily available. The batch mode adsorption studies were carried out by varying experimental parameters such as pH, initial dye concentration, contact time and temperature. The kinetic data at different concentrations and at different temperatures were analysed for both the adsorbents using pseudo first order and pseudo second order models. The equilibrium data were also analysed by Freundlich and Langmuir models. Thermodynamic studies were also evaluated. Finally, the performance of CSAC was compared with PPy/SD. The experimental results indicated that PPy/SD is most suitable for the removal of Acid Orange 7 from aqueous solutions than CSAC.